SILURIAN AND DEVONIAN HETEROCONCHIA CARDIOMORPHI BIVALVES FROM BOLIVIA (Ameghiniana, 2021)
Heteroconchia Cardiomorphi bivalves from Silurian and Devonian beds of the Central Andean Basin of Western Gondwana are herein presented. This paper is not only a systematic updated revision of three Heteroconchia Cardiomorphi genera, but it also includes the description of new findings and first reports of some taxa in the basin. They were collected in nine scattered outcrops in the Interandean and Subandean regions of Bolivia. A total of 22 specimens, well- to regularly-preserved was studied. The genus Pleurodapis, is reported for the first time from Ludlow–Pridoli successions of Alarache, southern Subandean as Pleurodapis sp. A. The cosmopolitan genus Paracyclas is reported in the Central Andean Basin for the first time, from the Middle Devonian of Subandean as Paracyclas? sp. The species Pleurodapis multicincta and Cardiomorpha oblonga, are described from the central Subandean and the Interandean regions for the first time in the basin. This research is also a contribution to understand the distribution and the richness of Silurian and Devonian bivalves in Central Andean Basin and their relations with the surrounding basins of Gondwana.